Utilization of pulverised coal monitoring system for cleaner electricity generation - Muhamad Said, Mohd. Farid (Universiti Malaysia Pahang, 2014)
This paper describes a utilization of the coal monitoring system, which is a clamp-on particle sizer (CPS) device for monitoring particle size at the outlet of a classifier model. The device is examined in terms of its capability to characterize moving particles in the classifier outlet pipe. The architecture and working principle of the device are explained. The device employs a high intensity continuous laser as a light source and a digital camera to capture the particle images. The image analysis technique has been implemented in extracting valuable information about the particles from the images. Image processing algorithms were applied in the development of the software and are described in this paper. In order to evaluate the repeatability of the CPS device technique, the measurement was repeated three times. The deviation result confirmed that the technique has a good repeatability in sizing the moving particles. Validation was performed by comparing the CPS with shadow device. Mean sizes obtained by the CPS device had differences of between 3.5 to 5% compared with the shadow device. The capacity of the CPS device was successfully examined by by measuring the small size and speed of the moving particles.